Response to foot and mouth disease (FMD) vaccination among local Malaysian cattle of various vaccination backgrounds from endemic and non-endemic FMD areas - Hamad, A. Abbo; Hassan, Latiffah; M. Z., Azmie; Loganathan, P.; Jaafar, T.; Arshad, Siti Suri; Hashim, J.; Amir, H.; Othman, Norlida; M. A., Syarifah Asiah; Salih, M. M. (Universiti Putra Malaysia Press, 2015)
A longitudinal study assessed the response to foot and mouth disease virus (FMDV) vaccination on sequential sera of local Malaysian Kedah-Kelantan cattle in two states of Peninsular Malaysia; Perlis, a foot and mouth (FMD) disease non-endemic state, and Kelantan, an endemic state for FMD. These cattle were from various vaccination backgrounds and some with unknown vaccination status. For the cattle in both states, the antibody against FMDV type O effectively increased to a strong protective level in the first week following vaccination, regardless of the vaccination background of the animals. In the endemic state, where vaccination was performed more routinely than the non-endemic state, the response had better magnitude and duration. In the non-endemic state, the antibody response level was good but appeared to last for a shorter period of time before it significantly declined. For naïve cattle with no evidence of infection or vaccination, the response was rapid and reached a strong level immediately by the first week. However, the level was not sustained and significantly declined thereafter. All the cattle stayed healthy and clinically FMD- free throughout the study, even when there was a transient evidence of natural field infection detected among the cattle. A marked difference was observed in the patterns of antibody response between cattle in the FMD endemic and non-endemic areas. However, the level of antibodies generally rose to a strong protective level within the stipulated 7-14 days post-vaccination. The vaccine used was effective in eliciting immune response when naturally challenged by the local field FMD virus.